Formation mechanisms of debris-flow material on slopes inroubar-e-ghasran, iran; a case study of the weathering impacts - Mosleh, Mojgan Hadi; Rafia, Farzan (Italian journal of engineering geology and environment, 2011)
Debris flows are widespread in many steep slopes in northeastern of Tehran province, Iran. The slopes in that region are mostly covered by a relatively thick mantle of weathered debris. Parent rocks mainly consist of vitric tuff and tuffaceous limestone of middle Eocene age. Several factors such as geomorphology, structural geology, tectonics and weathering as well as construction works trigger instability of slop in that area. Among various factors on the formation of debris-flow material, tectonics and weathering have been found to be the most influential factors.This study is focused on the formation mechanisms of debris-flow material and weathering indices of the parent rocks. The effects of weathering on some slopes in the first 15 km of the main road from Zardband to Meygoon were studied. Soil and rock samples were collected from the currently stable slopes as well as material from an old landslide. Geotechnical properties of the debris mantle were investigated using a series of field and laboratory tests. In addition, different weathering indices comprising of petrographical, engineering and chemical tests have been conducted in order to assess the most dominant type of weathering. Finally, it was concluded that mechanical weathering is the most in uential process in the formation of talus material in the study area.